Из записок разных лет - Ермолинский Сергей Александрович (Искусство, 1990)
Экземпляры: (20240115) / Инвентарный номер: 19858 / Цена: 5.00 / Сис.шифр: 83.3(2=Рус)7-8 Булгаков / Авт.знак: Е74 / ГРНТИ: 17 / ББК: 83.3(2=Рус)7-8 Булгаков